As trajetórias formativas de acadêmicos de educação física do curso de licenciatura da UFSM: contribuições na constituição do ser professor - Silva, Alexandra Rosa (2009)
The present study is inserted in to the Formation, Knowledge and Professional Development line of research of the Post-Graduation Program, Master‟s Degree in Education of the Universidade Federal de Santa Maria. It had the purpose of analyzing how the UFSM‟s academics of the Degree Course in Physical Education feel about their formative trajectories and the way how they mean these experiences, as well as the contributions of such experiences for the construction of their identities as forthcoming basic education professors. The methodology was characterized as a qualitative research in the form of a case study. We have made use of an elaborated interview composed by narratives of two academics enrolled in the discipline of Seminary in Supervised Curricular Apprenticeship . The analysis was focused on their experiences as students, the process of professional choice, and the formative experiences faced during the course of degree in Physical Education. The narrative of their formative trajectory in CEFD showed some marks of this formative path which produced several significances, besides contributing for the identification with the Physical Education and the being professor. The most emphasized marks during this formative process were the participation in study groups where the students had the chance of experience the research, the teaching and the extension; the supervised curricular apprenticeships and the criticism instigated by some professors in the classes. In that sense, we understand the educational learning as a plural learning composed by knowledge coming from various contexts, circumstances, and institutions, as well as from the personal and professional experience of the knowledge of disciplines and practical activities provided by the course. Thus, the formation courses are a starting point that cohabits with other formation possibilities because the formation must be understood as something that goes beyond the academical stage but does not do without it.